Considering the concept of grammatical metaphor in Spanish: reflexions on a contextually situated corpus - Wiefling, Fernanda (2023)
Fil: Wiefling, Fernanda. Universidad Nacional de Río Negro. Centro de Estudios de Lingüística, Literatura, su Aprendizaje y su Enseñanza (CELLAE). Río Negro; Argentina.